2018
DOI: 10.23986/afsci.67703
|View full text |Cite
|
Sign up to set email alerts
|

Yield responses to P fertilisation of onion (Allium cepa L.) and cabbage (Brassica oleracea Capitata Group L.) in Finland

Abstract: Finnish data on vegetable crops’ yield responses to phosphorus (P) applications are scarce, but P is usually applied in quantities that meet the crop demand with wide safety margins. We determined yield responses to P fertilisation of onion and cabbage at three sites in 3-year field trials. Only on a sandy loam with low P status did annual P applications give statistically significant yield increases, 7% and 20% over the P-unfertilised treatment for onion and cabbage, respectively. The maximum P rate allowed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
1
1
Order By: Relevance
“…Like our earlier study with onion and cabbage (Uusitalo et al 2018), also lettuce grown from transplants appears to have lower P demand than the limits of P use set by the FAEP. For onion and cabbage, field trials suggested that about half of the maximum P use limit of FAEP suffices to produce nearly maximum yield.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Like our earlier study with onion and cabbage (Uusitalo et al 2018), also lettuce grown from transplants appears to have lower P demand than the limits of P use set by the FAEP. For onion and cabbage, field trials suggested that about half of the maximum P use limit of FAEP suffices to produce nearly maximum yield.…”
Section: Discussionsupporting
confidence: 63%
“…Under northern growing conditions, vegetables are assumed to need high rates of P fertilisers, because of the short growing season and cold soils in spring. Nonetheless, an earlier Finnish study (Uusitalo et al 2018) suggested that P demand of vegetables such as onion and cabbage is smaller than previously thought also in Finland with our cryic soil temperature regime. In the study mentioned, statistically significant yield increases were found only on one of three sites, and P rates of 10-12 kg ha -1 were sufficient to produce 97% of yield maxima.…”
Section: Introductioncontrasting
confidence: 52%
“…Instead, the biomass harvested from PLM1.75 and PLM3.5 plots was, on average, twice (1,500–1,800 g/m 2 ) the biomass harvested from PLM0 plots or plots without mulching. However, weeds were not completely inhibited by PLM1.75 and PLM3.5 treatments and light and nutrient competition by weeds presumably reduced the yield as it remained below a typical yield of >3,000 g onion per m 2 in Finland (Uusitalo et al , 2018). Ecotoxicological risks of PL applied to soil have previously found to be small by Hagner (2013) and pyrolysis oils have recently been classified as readily biodegradable compounds by Campisi et al (2016).…”
Section: Discussionmentioning
confidence: 99%